The Effects of a Dietary Intervention with a Synbiotic Beverage on Women with Type 2 Diabetes, Overweight, or Obesity - Paola Rodríguez-Rugarcía; Leonel Cuamatzin-García; María de Lourdes Meza-Jiménez; Ma. del Rocío Baños-Lara; Diego Salatiel Zaragoza-Maldonado; Juan Carlos Rodríguez-Espinosa; Erika Lozada-Pérezmitre; Beatriz Pérez-Armendáriz (Fermentation)
Introduction: Non-communicable chronic diseases, such as overweight and obesity, are considered a high risk for type 2 diabetes. Globally, there are 536.6 million people with diabetes. Mexico has a high prevalence of these diseases. Objective: The objective of this study was to evaluate the effects of a synbiotic beverage and a 12-week dietary intervention on body composition and biochemical parameters in women with T2D, overweight, or obesity as an additional strategy for treatment. Methods: This was a double-blind, randomized, and experimental study of a 12-week dietary intervention with a synbiotic fermented beverage with n = 51 women divided into four groups: G1 followed a moderate calorie-restricted diet, G2 followed the same moderate calorie-restricted diet and consumed a synbiotic beverage, G3 only consumed the synbiotic beverage, and G4 consumed a placebo beverage. Results: Significant changes were seen in BMI (p < 0.001) and fat mass (kg) (%) (p < 0.001) after the 12-week dietary intervention, proving that the synbiotic beverage had an effect on body composition. Conclusions: Significant decreases in different body composition and biochemical profiles were seen, showing the benefits of the beverage. A dietary intervention and the consumption of a fermented beverage could be an additional treatment for non-communicable diseases.